The Arab World - Najib Ghadbian (American Journal of Islam and Society, 1994)
This book has an ambitious and comprehensive goal: to analyze the degenerate contemporary condition of the Arab nation and then present a “theory of action,” a vision to transcend the current state of decline and continue the process of nahdah. Barakat’s proposed approach to the analysis of Arab society is one that he characterizes as dynamic (treating society as changing rather than static), dialectical (emphasizing social contradictions and class struggle), and critical (aimed at transforming the status quo). He treats the Arab world as a single unit rather than as a number of nation-states. The emphasis on society rather than political entity does not negate his cognizance that the Arab world has the potential for both unity and divisiveness. Barakat arranges his analysis into three sections: Arab identity and issues of diversity and integration, social structures and institutions (i.e., family, social classes, religion, and Arab politics), and the dynamics of Arab culture. In his diagnosis of the Arab world’s maladies, Barakat offers interesting and useful insights. In making room for these insights, he blasts orientalist discourse for its “static and mosaic’’ portrait of the Arab world and presents a more cogent analysis of Arab reality. In fact, most orientalists do not acknowledge the existence of the Arab world, but speak rather of a “Middle East” that contains a dizzying array of religious, ethnic, and linguistic groups. They characterize the Arab part of this region as hopelessly divided, culturally inferior, and unable to modernize. Barakat points out that orientalists contradict themselves when they speak of both the divided nature of Arab society and the existence of an “Arab mind” or mentality. Moreover, most orientalist “scholarship” explains resistance to change among Arabs in terms of cultural attitudes, thereby ignoring the prevailing relationship of dependency and the socioeconomic and political contexts of this resistance. Such assertions “reveal the animosity toward Arabs (and especially toward Muslims) that underlies many scholarly pretensions” (p. 22). Barakat cleverly exposes the agenda behind such scholarship: the justification of Israel’s existence and the preservation of the status quo under Zionist and western hegemony ...